A case of parathyroid carcinoma mimicking parathyroid adenoma - Demirli Atıcı, Semra; Yeşilyurt, Değercan; Solakoğlu Kahraman, Dudu; Dikmeer, Emre; Öğücü, Hakan; Demir, Halit Batuhan; Akbulut, Gökhan (Journal of Surgery and Medicine, 2019)
Parathyroid carcinoma is one of the rare endocrine tumors and constitutes 1% of the cases with primary hyperparathyroidism. Because of similar imaging modalities and similar clinical findings, it is difficult to distinguish between preoperative parathyroid adenomas and parathyroid carcinoma. A 70-year-old female patient presented with fatigue and generalized bone pain. Her laboratory tests, neck and parathyroid scintigraphy were compatible with primary hyperparathyroidism with a significantly elevated level of parathormone. With the imaging methods which supported parathyroid adenoma, the patient was operated with a presumptive diagnosis of primary hyperparathyroidism due to parathyroid adenoma. The postoperative course was unremarkable and she was discharged on the postoperative fifth day. Postoperative pathology was reported as parathyroid carcinoma developed in a parathyroid adenoma. Parathyroid carcinoma and parathyroid adenoma have similar clinically and imaging methods, it is difficult to diagnose preoperatively.